2001
DOI: 10.1016/s0014-5793(01)03104-0
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase‐type plasminogen activator up‐regulates the expression of its cellular receptor through a post‐transcriptional mechanism

Abstract: We have recently reported that the urokinase-type plasminogen activator (uPA) up-regulates the cell surface expression of its own receptor (uPAR) in several cell types, independently of its enzymatic activity. uPA has no effect on kidney 293 cells which do not express uPAR and then cannot bind uPA. Kidney cells, transfected with the coding region of uPAR cDNA, express very large amounts of uPAR and respond to uPA stimulation by regulating uPAR both at mRNA and protein levels. uPA effect occurs also in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…We (28) and others (35,36) have shown that uPA induces the expression of uPAR in several cell types, including airway epithelial cells. Therefore, we hypothesized that uPA induced during sepsis enhances cell surface expression of uPAR in the lungs of LPSchallenged mice.…”
Section: Lps Enhances Upar Expression In Mouse Lung Tissue Through a mentioning
confidence: 72%
See 3 more Smart Citations
“…We (28) and others (35,36) have shown that uPA induces the expression of uPAR in several cell types, including airway epithelial cells. Therefore, we hypothesized that uPA induced during sepsis enhances cell surface expression of uPAR in the lungs of LPSchallenged mice.…”
Section: Lps Enhances Upar Expression In Mouse Lung Tissue Through a mentioning
confidence: 72%
“…We have previously observed that uPA enhances uPAR expression by post-transcriptional mRNA stabilization (35,36). Therefore, we next asked if LPS-induced expression of uPAR mRNA in Beas2B cells through this mechanism.…”
Section: Effect Of Lps On Upar Mrna Stability In Beas2b Cellsmentioning
confidence: 93%
See 2 more Smart Citations
“…26,27 Our results are in line with what is known about the ability of u -PA to up -regulate the expression of its cellular receptor at a transcriptional level, by increasing the activity of the transcriptional factor Sp1, and also at a posttranscriptional level, by promoting u -PAR mRNA stability. 28,29 The drop in u -PA would, therefore, down -regulate the expression of its receptor as detected in our experimental system. The expression of other genes, which could be related to the u -PA phenotype, such as PAI -1, t -PA, FN, and c -met (HGF receptor ), was also tested.…”
Section: Discussionmentioning
confidence: 59%